SISTEM INFORMASI PEMESANAN TIKET PADA INDAH TRAVEL BERBASIS WEB - Muhammad Khathab; Muh. Rasyid Ridha (Indragiri Islamic University, 2020)
Currently the development of technology is very rapid, many systems have been builtreal time and online information that allows users to accesswhere and whenever to get information. Beautiful travel is a servicetransactions that are still using the conventional way of booking tickets as wellsearch the departure schedule of a prospective passenger, i.e. through the window and viajust call. It is less effective both in terms of time and cost because it canthere is a discrepancy with customer desires. So that information systems are neededticket reservations that can provide clear information and are not limited by distance andtime. This study aims to build a ticket booking information system onwonderful web-based travel. The system development stage includes analysis, design,implementation and testing. The data collection method uses the study methodlibrary and observation. Ticket booking information system on beautiful web-based travelbuilt with the PHP programming language and Mysql database. This system was made forprovide ticket booking and departure schedule information. System test resultsnote that all functions contained in the system are running wellsuch as managing data, providing ticket lists, and purchasing and cancellation transactionsTicket reservations so that all the features provided can make it easy for customersand system operator